Pengaruh Penerapan Feeding Rules Terhadap Status Gizi Bayi Usia 6-12 Bulan di Klinik Pratama Hadijah - Meiliana, Meiliana; Siregar, Debi Novita; Wati, Mimi Midya; Hidayat, Maharani; Simanjuntak, Lusi Tania; Sinulingga, Esteria Latersia Br (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACTGrowth and development problems in toddlers are often underestimated bysociety, because it is considered normal if the child's weight is sufficient or inaccordance with standards (K.Suarayasa, dkk, 2022). Basic feeding rules areindirect factors that affect nutritional status. Therefore, feeding patterns havea close relationship with the nutritional status of children, with good foodconsumption and feeding patterns by parents and foods that contain importantelements for the child's body such as energy sources, builders and regulatorsthat help improve the condition and nutritional status of children better The purpose of this study was to determine the effect of the Application of Feeding Rules on the Nutritional Status of Infants aged 6-12 months. In making this study using quantitative research using pre-test and posttest one group design with a Quasi-Experimentaldesign without a control group that compares the results of evaluation beforeand after treatment of respondents. Data collection used Feeding Patternquestionnaire sheet and KMS Sheet to measure Nutritional Status in infants. Thestatistical test used is the Wilcoxon Signed Rank Test. The measurement resultsshowed that after the application of feeding rules there was a decrease inNutritional Status of Infants (P vallue = <0.002), namely as many as 25 infants(83.3%) with good nutritional status, 5 infants (16.6%) with less nutritionalstatus, 3 infants (10%) with more nutritional status and 2 infants (6.6%) withobese nutritional status. Based on the research that has been carried out, it isconcluded that there are differences from the nutritional status category beforethe application of feeding rules and after the application of feeding rules,namely an increase in the nutritional status of infants who are in the categoryof good nutrition.Keywords: Application of Feeding Rules, Nutritional Status of InfantsABSTRAKMasalah tumbuh kembang pada balita seringkali dianggap remeh olehmasyarakat, karena dianggap normal apabila berat badan anak mencukupi atausesuai dengan standar (K.Suarayasa, dkk, 2022). Praktik pola pemberian makanatau Basic Feeding rules merupakan faktor secara tidak langsung yangmempengaruhi status gizi. Oleh karena itu, pola pemberian makan memiliki hubungan erat dengan status gizi anak, dengan konsumsi makanan dan poa pemberian makan yang baik oleh orang tua serta makanan yang mengandung unsur- unsur penting bagi tubuh anak seperti sumber zat tenaga, pembangun dan pengatur iniah yang membantu memperbaiki kondisi dan status gizi anak lebih baik (Nobianti, 2018). Tujuan Penelitian ini untuk mengetahui pengaruh Penerapan Feeding Rules terhadap Status Gizi Bayi usia 6-12 bulan. Dalam membuat penelitian ini menggunakan penelitian kuantitatif yang menggunakan rancangan pre test dan posttest one group design, dengan rancangan Quasi Eksperimental tanpa kelompok kontrol yang membandingkan hasil evaluasi sebelum dan sesudah dilakukan perlakuan terhadap responden. Pengumpulan data menggunakan lembar kuisioner Pola Pemberian Makan dan Lembar KMS untuk mengukur Status Gizi pada bayi. Uji statistik yang digunakan adalah Wilcoxon Signed Rank Test. Hasil pengukuran menunjukkan bahwa setelah dilakukan penerapan feeding rules terdapat kenaikan status gizi bayi (P value = <0.002) yaitu sebanyak 25 bayi (83,3%) dengan status gizi baik, 5 bayi (16,6%) dengan status gizi kurang, 3 bayi (10%) dengan status gizi lebih dan 2 bayi (6,6%) dengan status gizi obesitas. Berdasarkan penelitian yang telah dilaksanakan maka didapatkan kesimpulan bahwa terdapat perbedaan dari kategori status gizi sebelum penerapan feeding rules dan sesudah penerapan feeding rules yaitu terjadi peningkatan status gizi bayi yang berada di kategori gizi baik.Kata Kunci: Penerapan Feeding Rules, Status Gizi Bayi